Mediating Effects of Psychological Independence and Social Support on the Association Between Family Strength and Depression in Young Korean Adults: Cross-Sectional Study - Sunyoung Kim; Suin Park; Hyunlye Kim; Dabok Noh (JMIR Formative Research, 2025)
Abstract BackgroundAlthough family strength is potentially associated with a reduced risk of depression, little is known about the underlying pathways and mediating factors. ObjectiveThis study aimed to investigate the mediating effects of psychological independence and social support on the relationship between family strength and depression in young adults. MethodsA cross-sectional web-based survey was conducted among 1,000 young Korean adults aged 19 to 24 years. We used a web-based survey agency to recruit participants using an independent panel and quota sampling, with stratification based on gender and age. The participants completed self-reported questionnaires that assessed family strength, psychological independence, social support, and depression. To examine the mediating effects of psychological independence and social support on the relationship between family strength and depression, we performed path analysis with AMOS 26 software (IBM Corp) using maximum standard likelihood estimation. ResultsThe path analysis revealed that gender (female) had a direct positive effect on depression (βPPβPPPPPPP ConclusionsThe findings highlight that gender, living with parents, family strength, psychological independence, and social support in reduce depression among young adults. Additionally, the mediating effects of psychological independence and social support on the relationship between family strength and depression were significant in this population. Therefore, strategies to increase psychological independence and social support could reduce the risk of depression in young adults who have low family strength.